2015
DOI: 10.5194/se-6-929-2015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hydraulic properties and plant coverage of the closed-landfill soils in Piacenza (Po Valley, Italy)

Abstract: Abstract. In this paper the results of a study of soil hydraulic properties and plant coverage of a landfill located in Piacenza (Po Valley, Italy) are presented, together with the attempt to relate the hydraulic properties in relation with plant coverage. The measured soil water retention curve was first compared with the output of pedotransfer functions taken from the literature and then compared with the output of the same pedotransfer functions applied to a reference soil. The landfill plant coverage was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…It is well known that management determines the infiltration rates in agricultural soils (Wang et al, 2015;Shi et al, 2015;Hazbavi and Sadeghi, 2016) and that as we found at the Valencia study site, there was a clear influence of vegetation on soil properties due to the improvement of soil quality by litter and root additions (de Boever et al, 2014) and an impact on runoff generation and hydraulics (Zhao et al, 2015). This positive impact of vegetation can be seen in agricultural soils, but also in restored mine soils and landfills (Cassinari et al, 2015;Thomas et al, 2015). In forest soils, the impact of vegetation type and biomass is also definitive to understanding the infiltration capacity of soils.…”
Section: Soil Hydrology and Erosion After Abandonmentsupporting
confidence: 58%
“…It is well known that management determines the infiltration rates in agricultural soils (Wang et al, 2015;Shi et al, 2015;Hazbavi and Sadeghi, 2016) and that as we found at the Valencia study site, there was a clear influence of vegetation on soil properties due to the improvement of soil quality by litter and root additions (de Boever et al, 2014) and an impact on runoff generation and hydraulics (Zhao et al, 2015). This positive impact of vegetation can be seen in agricultural soils, but also in restored mine soils and landfills (Cassinari et al, 2015;Thomas et al, 2015). In forest soils, the impact of vegetation type and biomass is also definitive to understanding the infiltration capacity of soils.…”
Section: Soil Hydrology and Erosion After Abandonmentsupporting
confidence: 58%
“…Soil hydraulic conductivity is mainly affected by its structural (Zhou et al, 2008;Moncada et al, 2014;Schwen et al, 2014) and chemical characteristics (Ahmad et al, 2015;Shi et al, 2015). Reduced aggregate stability and lowered hydraulic conductivity can be responsible for severe soil erosion and other forms of land degradation (Mainuri and Owino, 2013;Mahmoodabadi and Cerdà, 2013;Arjmand Sajjadi and Mahmoodabadi, 2015a,b) and is clearly dependent on vegetation cover (Cassinari et al, 2015;De Boever et al, 2014;Ola et al, 2015). In most agricultural areas, soil organic carbon (SOC) enhances hydraulic conductivity by improving aggregate stability and porosity (Le Bissonnais et al, 2007;Mahmoodabadi and Ahmadbeygi, 2013;Eibisch et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Determining soil hydraulic properties is necessary for interpreting and simulating many hydrological processes having environmental and economic importance (Turner et al, ), such as rainfall partition into infiltration and runoff (Cassinari, Manfredi, Giupponi, Trevisan, & Piccini, ; Iovino, Castellini, Bagarello, & Giordano, ; Rockström, Jansson, & Barron, ). The saturated soil hydraulic conductivity, K s , exerts a dominating influence on the partitioning of rainfall in vertical and lateral flow paths.…”
Section: Introductionmentioning
confidence: 99%